1995
DOI: 10.1002/chin.199530263
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Convenient Route to D‐Apio‐β‐D‐furanosyl‐ and 2′‐Deoxyapio‐. beta.‐D‐furanosyl Nucleosides.

Abstract: A Convenient Route to D-Apio-β-D-furanosyl-and 2'-Deoxyapio-. beta.-D-furanosyl Nucleosides.-Some title compounds like (VI) and (VII) are prepared via an efficient formation of the triacetate (IV). They do not show antiviral activity against HIV and Herpes simplex. -(HAMMER-SCHMIDT, F.; OEHLER, E.; POLSTERER, J.-P.; ZBIRAL, E.; BALZARINI, J.; DECLERCQ, E.; Liebigs Ann.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…20−22 Later studies showed that the pyrimidine counterparts 4b−d are inactive against a panel of viruses (e.g., HIV-1, HIV-2, HSV-1, HSV-2, VV, and VSV). 23 Watson et al evaluated the epimers 5a−e against T-lymphocyte proliferation and HSV. 24 Compound 5a significantly reduces HSV-2 plaque formation in BHK cells (42% reduction at 4 μM), while 4a does not.…”
Section: Nucleosides With a Transposed 4′-hydroxymethyl Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…20−22 Later studies showed that the pyrimidine counterparts 4b−d are inactive against a panel of viruses (e.g., HIV-1, HIV-2, HSV-1, HSV-2, VV, and VSV). 23 Watson et al evaluated the epimers 5a−e against T-lymphocyte proliferation and HSV. 24 Compound 5a significantly reduces HSV-2 plaque formation in BHK cells (42% reduction at 4 μM), while 4a does not.…”
Section: Nucleosides With a Transposed 4′-hydroxymethyl Groupmentioning
confidence: 99%
“…Also the enantiomeric 2′-deoxy compounds 7a−c and their anomers 8a−c were also found inactive. 23,25 The D-and L-3′-deoxyapionucleosides 9a−e and 10a−c failed to inhibit DNA or RNA viruses (e.g., HIV-1, HIV-2, HSV-1, HSV-2, VV, and VSV) and, unlike their 2′-deoxy regiomers 6a−c, show no cytotoxicity. 26 Later Jung et al found 9b active against HSV-1(KOS) (MIC 50 = 39.6 μM) and 9e active against HSV-1 in two different cell lines, i.e., KOS and 2(G) (MIC 50 = 7.1 and 35.9 μM, respectively).…”
Section: Nucleosides With a Transposed 4′-hydroxymethyl Groupmentioning
confidence: 99%